Adoption of New BRI Care: A Review Based on Theoretical Frameworks Analysis - Rahadi, Hadrian; Herawati, Berlian Ferra; Perdhana, Mirwan Surya (Research Horizon, 2025)
The adoption of internal digital platforms has become increasingly essential amid the rapid digital transformation in the banking sector. However, many innovations fail due to low user acceptance, especially when employee readiness and organizational capacity are overlooked. In response to this challenge, this study investigates the key factors influencing the adoption of the new BRI Care application, a customer handling management system developed by PT Bank Rakyat Indonesia (Persero) Tbk. Despite the platform’s potential to streamline complaint resolution, empirical research on internal user adoption remains limited. Addressing this gap, the study employs a literature review methodology grounded in the Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology, and Diffusion of Innovation frameworks. The synthesis reveals that perceived usefulness and perceived ease of use are consistent predictors of adoption intention. Additionally, organizational support, user training, and system usability emerge as enabling factors, while positive user experience and effective complaint resolution reinforce sustained use. The findings offer strategic insight for aligning digital tools with user needs, ultimately enhancing service quality and operational efficiency.